The unfortunates : a novel - Chukwu, J K. (Harper, an imprint of HarperCollinsPublishers, 2023)
Sahara, a queer, half-Nigerian college sophomore who feels like an all-around failure, finds hope, answers, and unexpected redemption when she sets out to find the truth about The Unfortunates--the unlucky subset of black undergrads who have been mysteriously disappearing.